Importanţa modelelor animale în cercetarea oncologică: Un review / The importance of animal models in oncological research: A review - Diana Mihaela Alexandru; Ana-Maria Coman; Răzvan Dobre; Maria Crivineanu (Medicamentul Veterinar, 2020)
In oncology research, in vivo experiments on animal models have played and still play an essential role in understanding the etiology, evolution, diagnosis and therapy of human cancer. The purpose of this review is to highlight the importance of preclinical oncological studies on both experimental animals and pets that have developed spontaneous tumours, in the evolution of diagnostic methods and therapeutic management of neoplastic diseases. Also, a series of criteria underlying the elaboration of an in vivo study are emphasized, regarding the species, breed, sex, age of the animals, the selected tumour line and its purpose, taking into account the obligation to respect the ethical principles regarding the use of animals in research.